Greenhouse Ventilation - Jonathan A. Watson; Celina Gómez; D. E. Buffington; Ray A. Bucklin; Richard W. Henley; Dennis B. McConnell (EDIS, 2019)
Greenhouse ventilation involves removing air from inside the greenhouse and replacing it with outside air. The ventilation may be natural (caused by wind and temperature forces) or mechanical (accomplished by using fans). The purposes of ventilation are to control high temperatures during the summer caused by the influx of solar radiation, to maintain relative humidity at acceptable levels during winter, to provide uniform air flow throughout the greenhouse, and to maintain acceptable levels of gas concentration in the greenhouse. Ventilation systems for greenhouses must be considered for three climatic conditions that typically occur during the year—winter, summer, and spring–fall. This 4-page fact sheet is a minor revision written by J. A. Watson, C. Gómez, D. E. Buffington, R. A. Bucklin, R. W. Henley, and D. B. McConnell, and published by the Department of Agricultural and Biological Engineering, November 2019.